Microsimulation of Private Health Insurance and Medicaid Take-Up Following the U.S. Supreme Court Decision Upholding the Affordable Care Act - Parente, Stephen T (Blackwell Science Inc, 2013)
OBJECTIVE: To predict take-up of private health insurance and Medicaid following the U.S. Supreme Court decision upholding the Affordable Care Act (ACA). DATA SOURCES: Data came from three large employers and a sampling of premiums from http://ehealthinsurance.com. We supplemented the employer data with information on state Medicaid eligibility and costs from the Kaiser Family Foundation. National predictions were based on the MEPS Household Component. STUDY DESIGN: We estimated a conditional logit model of health plan choice in the large group market. Using the coefficients from the choice model, we predicted take-up in the group and individual health insurance markets. Following ACA implementation, we added choices to the individual market corresponding to plans that will be available in state and federal exchanges. Depending on eligibility for premium subsidies, we reduced the out-of-pocket premiums for those choices. We simulated several possible patterns for states opting out of the Medicaid expansion, as allowed by the Supreme Court. PRINCIPAL FINDINGS: The ACA will increase coverage substantially in the private insurance market and Medicaid. HSAs will remain desirable in both the individual and employer markets. CONCLUSIONS: If states opt out of the Medicaid expansion, this could increase the federal cost of health reform, while reducing the number of newly covered lives.